On Janowski starlike functions - Çağlar, Mert; Şen, A.; Owa, Shigeyoshi; YAVUZ, EMEL; POLATOĞLU, YAŞAR (Springer International Publishing Ag, Gewerbestrasse 11, Cham, Ch-6330, Switzerland, 2007)
For analytic functions f(z) in the open unit disc U with f(0) = 0 and f'(0) = 1, applying the fractional calculus for f(z), a new fractional operator D-lambda f(z) is introduced. Further, a new subclass F-lambda(*)(A, B) consisting of f(z) associated with Janowski function is defined. The objective of the present paper is to discuss some interesting properties of the class F-lambda(*)(A, B). Copyright (c) 2007.
Keywords: Starlike functions; fractional calculus